(untitled) (Regional aspects of productive forces development of Ukraine, 2019)
The article substantiates the economic essence of food security as the main strategic priority of the economic development of the agrarian sector of the Ukrainian economy. Her place in the system of economic security is shown and conditions for reaching its high level are highlighted. The principles of increasing the level of food security are formulated and the dynamics of foreign trade turnover of agrarian sector products in the period from 2000 to 2016 is analyzed. The main directions of formation of the export potential of the investigated sector of the economy in the conditions of globalization are singled out.